Sex differences in asthma and gastroesophageal reflux disease incidence among the World Trade Center Health Program General Responder Cohort. Issue 9 (18th July 2016) - Jiang, Jieying; Icitovic, Nikolina; Crane, Michael A.; Dasaro, Christopher R.; Kaplan, Julia R.; Lucchini, Roberto G.; Luft, Benjamin J.; Moline, Jacqueline M.; Pendem, Lakshmi; Shapiro, Moshe; Udasin, Iris G.; Todd, Andrew C.; et al.
Abstract : Background: Asthma and gastroesophageal reflux disease (GERD) are two common conditions among the responders to the WTC attacks. This study examined whether the cumulative incidence rates of asthma and GERD differed by sex among 24, 022 and 23, 557 WTC responders, respectively. Methods: Cox proportional hazards regression was used to examine the sex difference in the rate of onset of physician‐diagnosed asthma or GERD, from 9/12/2001 through 12/31/2015. Results: The cumulative incidence of asthma reached 23% for women and 17% for men by the end of 2015, and the cumulative incidence of GERD reached 45% for women and 38% for men. Comparing women to men, the hazard ratio was 1.48 (95% confidence interval (CI): 1.27, 1.74) for asthma, and 1.25 (95% CI: 1.13, 1.38) for GERD. Conclusions: WTC general responders have a substantial burden of asthma and GERD, with higher incidence in women. Am. J. Ind. Med. 59:815–822, 2016. © 2016 Wiley Periodicals, Inc.